Fostering Social Innovation for Quality of Life Building in Two Generations - Chittra Chanakul; Washiraporn Wannachot; Veena Prachagool; Prasart Nuangchalerm (Journal of Educational Issues, 2024)
The influence of digital technology and sociocultural adaptation is currently quickly changing society. Understanding the disparities between generations was necessary for moving on to the next generation together. The purposes of this research were to 1) study patterns of improving the quality of life of the elderly in different family styles, and 2) develop a curriculum of self-awareness in bringing the parenting skills of the aging population to early childhood using contemplative education. Data were collected by using questionnaires from 285 elderly northeast people in one province of Thailand, semi-structured interviews conducted with 22 elderly people. The curriculum of self-awareness used Delphi technique to assess its the appropriateness. Six key attributes were reported in learning participation, acceptance of original experiences, self-guided learning, critical thinking, action, and reflection. Elderly needed self-development for applying knowledge and skills to correct actual parenting situations.